Anatomy and dendrometry of wood of Pterodon polygalaeflorus and P. pubescens - de Paula, José Elias; Cardoso, Edimar Nery (Pesquisa Agropecuaria Brasileira, 1995)
The study was based on three areas from the internal part of circulate sample of trunk towards the periphery. The basic density of the tree areas of stem in Pterodon polygalaeflorus was as follows: area 1, 861 kg/m3, area 2 and 3, 964 kg/m3, whereas that of P. pubescens was: area 1, 750 kg/m3; area 2, 1.009 kg/m3 and area 3, 1.116 kg/m3. Dry wood yields per inventoryed 20 trees were of 8.720 tons of P. polygalaeflorus and of 7,311 tons of P. pubescens. The fibers percentage in the trunk of P. polygalaeflorus were 51,1%, 63,6% and 68,2% respectively area 1, area 2 and area 3; in P. pubescens these percentages were: area 1, 37,5%, area 2, 54,5% and area 3, 56,5%.